A Study on Hydrodynamic Behaviour of SW Coast of India – Implication to Ecosystem Model. (2015) - Rao, V. Ranga; Ramu, K.; Dash, S.K.; Patra, S.; Vishnuvardhan, K.; Rao, V. Damodara; Mohan, R.
Abstract: Integrated Coastal and Marine Area Management – Project Directorate (ICMAM-PD), Ministry of Earth Sciences, Govt of India is implementing a project on ecosystem modelling for SW Coast of India to study the anthropogenic and natural influences on ecosystem character of SW Coast of India during the 12th plan period (2012-17). The study area covers the coastal stretch from Goa to Kanyakumari including the offshore waters, the estuarine and the inlet waters. In order to develop an ecosystem model for the SW Coast, extensive data sets on various physical and biogeochemical parameters (water levels, currents, temperature, salinity, nutrients, DO, chlorophyll, primary production etc) have been collected since 2012 through various field measurements. The available past data from ICMAM database, COMAPS datasets, institutional reports etc have also been collected to understand the hydrodynamic behaviour of the SW Coast. The hydrodynamic processes such as tidal propagation, currents and circulation, density distribution, etc have been studied to understand the dispersal mechanisms of particulate matter derived from land run off. Model simulations were carried out to investigate the dynamics of the shelf flow response to the spatial and temporal variability of the tidal forcing along the SW Coast. An attempt has been made to understand the variability of the surface circulation and associated SSC in different seasonal condition during 2013 and 2014 as a response of wind and tidal forcing under variable land run off conditions. Temperature, salinity, and density profiles were used to study the variability in circulation and stratification characteristics along the coast. Tide models were utilized to study the tidal excursion along the coast and the results were validated with the tide data from the survey of India. The regions of hydraulic heads, and zones of possible accumulation of particulate matter along the coast and the subsequent influences on ecosystem character has been studied and discussed.